2016
DOI: 10.1177/1541931213601378
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating ANSI Z535-Formatted Warning Labels as an Integrative System

Abstract: Debate continues regarding the relative effectiveness of the ANSI Z535 guidelines for the design and placement of warnings. Research shows consistent positive effects of these guidelines on precursors to warning compliance (e.g., noticing, reading, intended compliance), but less consistency on compliance behavior. Challenges in interpreting these findings stem from factors such as small sample sizes, varying research designs and experimental conditions, and treating the ANSI Z535 guidelines as a singular entit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Had the manufacturer conducted such a design and evaluation process and effectively guarded users from the product hazards, it is most likely that the man in the subject forensic case, and others like him, would not have been injured or killed by foreseeable use of this product. (Adams & Edworthy, 1995;Braun, Sansing, Kennedy, & Silver, 1994;Braun & Silver, 1995;Chapanis, 1994;Desaulniers, 1987;Frantz, 1993;Godfrey et al, 1991;Jaynes & Boles, 1990;Kalsher, Obenauer & Weiss, 2016;Laughery & Stanush, 1989;Laughery, Vaubel, Young, Brelsford, & Rowe, 1993;Morrow, Leirer, Andrassy, Hier, & Menard, 1998;Nemire, 2016;Otsubo, 1988;Wogalter et al, 1987;Wogalter, Begley, Scancorelli, & Brelsford, 1997;Wogalter, Kalsher, & Racicot, 1992;Wogalter & Rashid, 1998;Young, 1991). Part of the problem with the warnings on the subject can of denatured alcohol is that the labeling of this hazardous product, and others, falls under the auspices of the FHSA, which is administered by the Consumer Product Safety Commission (CPSC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Had the manufacturer conducted such a design and evaluation process and effectively guarded users from the product hazards, it is most likely that the man in the subject forensic case, and others like him, would not have been injured or killed by foreseeable use of this product. (Adams & Edworthy, 1995;Braun, Sansing, Kennedy, & Silver, 1994;Braun & Silver, 1995;Chapanis, 1994;Desaulniers, 1987;Frantz, 1993;Godfrey et al, 1991;Jaynes & Boles, 1990;Kalsher, Obenauer & Weiss, 2016;Laughery & Stanush, 1989;Laughery, Vaubel, Young, Brelsford, & Rowe, 1993;Morrow, Leirer, Andrassy, Hier, & Menard, 1998;Nemire, 2016;Otsubo, 1988;Wogalter et al, 1987;Wogalter, Begley, Scancorelli, & Brelsford, 1997;Wogalter, Kalsher, & Racicot, 1992;Wogalter & Rashid, 1998;Young, 1991). Part of the problem with the warnings on the subject can of denatured alcohol is that the labeling of this hazardous product, and others, falls under the auspices of the FHSA, which is administered by the Consumer Product Safety Commission (CPSC).…”
Section: Discussionmentioning
confidence: 99%
“…(Adams & Edworthy, 1995; Braun, Sansing, Kennedy, & Silver, 1994; Braun & Silver, 1995; Chapanis, 1994; Desaulniers, 1987; Frantz, 1993; Godfrey et al, 1991; Jaynes & Boles, 1990; Kalsher, Obenauer & Weiss, 2016; Laughery & Stanush, 1989; Laughery, Vaubel, Young, Brelsford, & Rowe, 1993; Morrow, Leirer, Andrassy, Hier, & Menard, 1998; Nemire, 2016; Otsubo, 1988; Wogalter et al, 1987; Wogalter, Begley, Scancorelli, & Brelsford, 1997; Wogalter, Kalsher, & Racicot, 1992; Wogalter & Rashid, 1998; Young, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…This warning label was designed according to the guidelines of the American National Standard Institute's (ANSI's) warning label standard, ANSI Z535.4. ANSI-styled warnings are based on the latest peer-reviewed research on warning labels and have shown often to be more effective than other formats or labels that do not follow ANSI guidelines [ 16 ]. Conversely, according to previous research, the content and design of current tanning bed warning labels have not been informed by health communication best practices, are not based on research [ 17 ], and may be hard to see or missing [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Procedure. We will provide a summary of the procedure as it has been described in detail by Kalsher, Obenauer, and Weiss (2016). Participants were given a six-page packet that included a set of instructions, images of warning labels, an image of a file cabinet, and questions pertaining to both the participants' experience with file cabinets and their demographic characteristics.…”
Section: Methodsmentioning
confidence: 99%